Risk-Adapted Anesthesia and Sympathetic Attenuation in Geriatric Cardiometabolic Multimorbidity: Navigating the Limited Physiologic Reserve - Luh Ayu Mahetri; Ketut Jayati Utami Dewi (HM Publisher, 2026)
Introduction: The aging surgical population is defined by homeostenosis, a critical reduction in physiologic reserve that leaves patients vulnerable to perioperative stressors. This vulnerability is exponentially increased by the cardiometabolic triad of hypertension, coronary artery disease, and type II diabetes mellitus. This report illustrates the management of these competing physiological demands during high-stress open abdominal surgery. Case presentation: A 71-year-old male, ASA III, body mass index 27 kg/m², with stage II hypertension, insulin-dependent type II diabetes, and ischemic heart disease, presented for open cholecystectomy. Preoperative functional capacity was less than 4 METs. Baseline ward blood pressure was 138/84 mmHg. Intraoperatively, surgical traction on the gallbladder mesentery precipitated a sympathetic surge, with systolic blood pressure spiking to 171/95 mmHg, representing a 24% increase from baseline mean arterial pressure, without compensatory tachycardia (heart rate stable at 83 bpm), indicative of autonomic neuropathy. Utilizing a risk-adapted protocol, anesthesia was deepened with Sevoflurane to 3.5% and a targeted Fentanyl bolus of 50 mcg was administered. This intervention successfully attenuated the surge, reducing systolic blood pressure to less than 150 mmHg within 4 minutes. A restrictive fluid strategy of 500 mL total input was employed. Postoperative renal function remained stable with a Creatinine of 1.05 mg/dL, and the patient was discharged with a pain score of 2 out of 10. Conclusion: Successful management of the geriatric vascular stiffness phenotype requires anticipating the dissociation between heart rate and blood pressure. Vigilant, physiologically-guided titration of volatile agents and opioids, rather than invasive technology alone, can mitigate myocardial ischemia in low-resource settings.